Estudos de parâmetros clínicos e patológicos em ovelhas infectadas por Trypanosoma vivax no início e final da gestação - Silva, Taciana de Melo Fernandes (2012)
This study aimed to investigate the effect of experimental infection with Trypanosoma vivax in ewes at different stages of pregnancy, to determine the pathogenesis of reproductive failure, and confirm transplacental transmission by PCR. A total of 12 pregnant ewes twelve, adults into three groups G1, consisting of three ewes infected in the first third of pregnancy, G2, consisting of three infected ewes in the final third of gestation, and G3, consisting of six non-infected sheep (control group .) Each ewes G1 and G2 were inoculated with trypomastigotes 1.25 x105. Clinical examination, assessment of hematocrit, serum chemistry, determination of plasma progesterone and parasitemia were determined daily. Pathological examinations were conducted of the fetus, placenta, umbilical cord blood and DNA detection of the parasite in the placenta, amniotic fluid, blood and tissues of fetuses. The parasitaemia was high, reaching peaks of 2.7 x106, being persistent throughout the experimental period. The infection was characterized by the ewes mortality and perinatal mortality in the first third; abortion and perinatal mortality in the final third of gestation. The factors possibly related maternal reproductive failures were low body score, hematocrit, serum glucose, total protein, cholesterol and progesterone. The presence of DNA of T. vivax in the blood and tissues of fetuses, placenta and amniotic fluid, confirming transplacental transmission of the parasite. The presence of histological lesions in the fetal organs and placenta suggest the involvement of the parasite in the pathophysiological mechanism of reproductive damage